Skill Development in NEP 2020: A Significant Dimension: NEP 2020 में कौशल विकास: एक महत्वपूर्ण आयाम - Gupta, Simran; Upadhyay, Vikrant (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Since the beginning of human civilization, humans have paved their way for livelihood through various activities. During this process, numerous discoveries have emerged through human actions, which have ultimately made life easier and more accessible. In the materialistic lifestyle of the modern era, the need for skills in human life naturally exists. With the continuous emergence of new technologies, the acquisition of knowledge and skills remains just as relevant today as it was in the early days for performing basic life-sustaining activities. Education contributes to the holistic development of human life and helps individuals acquire foundational skills for the future. From the Vedic educational system of the Indian knowledge tradition to the latest branch of Western philosophy, Marxism, all have considered the acquisition of skills through education essential and significant for human life. After India’s independence, various education commissions and policies have also laid down numerous regulations to promote skill acquisition through education. In this sequence, the National Education Policy (NEP) 2020 has recognized the importance and necessity of skill development in the education of children and youth, and has made several policy decisions for its integration into the school curriculum. Through this research paper, the scholar has attempted to highlight skill development as a significant dimension of the New Education Policy 2020. Abstract in Hindi Language: मानव सभ्यता के आरंभ से ही मनुष्य ने अपनी क्रियाकलापों से जीवन यापन हेतु अपना मार्ग प्रशस्त किया है । इस दौरान मनुष्य द्वारा अनेक क्रियाओं के माध्यम से विभिन्न खोजों को जन्म दिया गया है जिसके फलस्वरुप मानव जीवन सरल व सुगम्य हो सका । आधुनिक युग की भौतिकतावादी जीवनशैली में मानव जीवन हेतु क्रिया-कौशलों की आवश्यकता स्वत: ही विद्यमान है। नित नई-नई प्रौद्योगिकी के आने से मानव को उसके ज्ञान एवं कौशल का अर्जन करना आज भी उतना ही प्रासंगिक है जितना कि प्रारम्भिक काल में जीवनयापन हेतु आधारभूत क्रियाओं को सम्पन्न करना । शिक्षा मानव जीवन का सर्वांगीण विकास करते हुए उसे आगामी भविष्य हेतु आधारभूत क्रिया-कौशलों का ज्ञानार्जन करने में सहायक होती है। भारतीय ज्ञान परम्परा के वैदिकालीन शिक्षा व्यवस्था से लेकर पाश्चात्य दर्शन की नवीनतम शाखा मार्क्सवाद तक सभी ने शिक्षा में क्रिया-कौशलों के ज्ञानार्जन को मानव जीवन के लिए आवश्यक एवं महत्वपूर्ण माना है। भारतीय स्वतंत्रता के पश्चात् विभिन्न शिक्षा आयोग एवं शिक्षा नीतियों ने भी शिक्षा द्वारा क्रिया-कौशल के अर्जन पर अनेक नियमन निर्धारित किए । इसी क्रम में राष्ट्रीय शिक्षा नीति 2020 ने भी बालकों एवं युवाओं की शिक्षा में कौशल विकास को महत्वपूर्ण व आवश्यक समझते हुए विद्यालयी पाठ्यक्रम में इसके समावेशन हेतु अनेक नीतिगत निर्णय लिए हैं। प्रस्तुत शोध पत्र के द्वारा शोधार्थी ने नई शिक्षा नीति 2020 के एक महत्वपूर्ण आयाम कौशल विकास को रेखांकित करने का प्रयास किया है। Keywords: कौशल विकास, शिक्षा नीति, नई शिक्षा नीति 2020